Nutritional Status Of Under 5 Children And Associated Factors Of Kunchha Village Development Committee - Dhungana, Govinda Prasad (Journal of Chitwan Medical College, 2014)
The study was under taken to assess nutritional status of children and identify the associated factors. Nutritionalstatus of children age 12-59 month was assessed using anthropometric measurement namely weight, height and mid upper arm circumference (MUAC) using standard procedure. To identify the factor, semi structural questionnaire was used for the mothers. Sixty percent of children had normal nutritional status and 40% followed by some malnutrition status by Gomez classification. No of ANC visit (odd ratio = 7.54 and 95% CI was 1.37 - 41.41), practice during the pregnancy period (P value < 0.021), and feeding practice of extra milk to the children (P value < 0.037) was significantly associated factors. Journal of Chitwan Medical College 2013; 3(4); 38-42 DOI: http://dx.doi.org/10.3126/jcmc.v3i4.9553